Democracy and association - Warren, Mark (Mark E.) (Princeton University Press, 2001)
Tocqueville's view that a virtuous and viable democracy depends on robust associational life has become a cornerstone of contemporary democratic theory. Democratic theorists generally agree that issue networks, recreational associations, support circles, religious groups, unions, advocacy groups, and myriad other kinds of associations enhance democracy by cultivating citizenship, promoting public deliberation, providing voice and representation, and enabling varied forms of governance. Yet there has been little work to show how and why different kinds of association have different effects on democracy -- many supportive but others minimal or even destructive.